Perbedaan Ekspresi Emosi Pada Beberapa Tingkat Generasi Suku Jawa di Yogyakarta - Aditya Putra Kurniawan; Nida Ul Hasanat (Faculty of Psychology, Universitas Gadjah Mada, 2007)
The objec¬tive of this research is to find whether, there are differences of emotion expression in three generation of Javanese culture in Yogya¬karta. This research is a quanti¬tative study, using Display Rules Assessment Inventory (DRAl). The subjects of this study were late adolescent, early adulthood and middle adulthood who were born and live in Yogyakarta. The result of this research shows, there was no difference of emotion expression in different generation of Javanese culture in Yogyakarta (F = 1,042 ; P = 0,356;). All three generation expressed emotion in the same way. This result describes that three generation categories who have been researched are still in the same norms on display rules of emotion in all situation. The researcher argue that the result is influenced by Javanese culture. The Javanese values of respect and the maintenance of social harmony (rukun) are base on principles of normative and moral guidance for social interaction within both the family and community. The strong emphasis on rukun (social harmony) has marked the typical Javanese as inexpressive, avoiding social and personal conflict. These values virtues contribute to harmonious social integration. Ideal human virtues include obedience to superiors (manut), generosity, avoidance of conflict, understanding of others, and empathy. These moral compo¬nents and values that colourize Javanese society are internalized by the children during the earliest years, and significant forces motivating the child's behaviour later in adulthood. Keywords: Expression emotion, three generation (late adolescent, early adulthood and middle adulthood), Javanese culture.